2002
DOI: 10.1089/105072502753451896
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the CTLA-4 Gene Is Associated with Autoimmune Hypothyroidism in the United Kingdom

Abstract: The cytotoxic T-lymphocyte-associated-4 (CTLA-4) molecule plays an important role in immune regulation by downregulating activation of T cells by antigen-presenting cells. Polymorphisms of the CTLA-4 gene have been shown to be associated with susceptibility to a number of autoimmune diseases. Some, but not all, studies suggest association between the CTLA-4 gene and autoimmune hypothyroidism. The aim of this study was to determine whether allelic association was present between the A-G single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 25 publications
2
36
0
4
Order By: Relevance
“…Analysis of 48 multiplex families, of which 46 were white, 20 had at least two members with Hashimoto thyroiditis and 17 had one sibling affected by Hashimoto thyroiditis, showed no linkage between the CTLA4 (AT) n repeat polymorphism and autoimmune hypothyroidism (Nithiyananthan et al 2002). A whole-genome scan using a subset of 42 families (22 comprising only Hashimoto thyroiditis-affected members, and 20 with one child affected by Hashimoto thyroiditis) from 56 white multiplex AITD families mapped three regions of linkage with autoimmune hypothyroidism on chromosome 6p (AITD-1 susceptibility locus), 12q22 [Hashimoto thyroiditis (HT)-1 locus] and 13q22 (HT-2 locus), and showed no linkage to chromosome 2q33, where the CTLA4 gene is located (Tomer et al 1999).…”
Section: The Ctla4 Gene and Susceptibility Of Diseasementioning
confidence: 97%
See 2 more Smart Citations
“…Analysis of 48 multiplex families, of which 46 were white, 20 had at least two members with Hashimoto thyroiditis and 17 had one sibling affected by Hashimoto thyroiditis, showed no linkage between the CTLA4 (AT) n repeat polymorphism and autoimmune hypothyroidism (Nithiyananthan et al 2002). A whole-genome scan using a subset of 42 families (22 comprising only Hashimoto thyroiditis-affected members, and 20 with one child affected by Hashimoto thyroiditis) from 56 white multiplex AITD families mapped three regions of linkage with autoimmune hypothyroidism on chromosome 6p (AITD-1 susceptibility locus), 12q22 [Hashimoto thyroiditis (HT)-1 locus] and 13q22 (HT-2 locus), and showed no linkage to chromosome 2q33, where the CTLA4 gene is located (Tomer et al 1999).…”
Section: The Ctla4 Gene and Susceptibility Of Diseasementioning
confidence: 97%
“…The linkage of CTLA4 to Graves' disease was confirmed using an enlarged set of 179 UK families (Heward et al 1999). However, family studies showed no linkage between the CTLA4 locus and Graves' disease in other populations (Maalej et al 2001, Sakai et al 2001, Nithiyananthan et al 2002, Tomoyose et al 2002, Villanueva et al 2002. It thus remains questionable whether the CTLA4 gene is linked to the disease.…”
Section: The Ctla4 Gene and Susceptibility Of Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…Whereas the CD28 ligand interaction plays a critical role in increasing and maintaining the T cell response initiated through engagement of the T cell receptor (TCR), the CTLA4 ligand interaction has an inhibitory effect on T cell activation and might contribute to peripheral tolerance. CTLA4 single nucleotide polymorphisms (SNPs) within the gene have consistently been found to be associated with Graves' disease (GD), 5 type 1 diabetes (T1D), 5 autoimmune hypothyroidism (AIH), 6 systemic lupus erythematosus (SLE), 7 and Addison's disease. 8 Several polymorphisms have been described in CTLA4, including À1722T/C and À319C/T, both of which are located within the promoter region, þ49A/G in exon 1 (rs 231775), 9 polymorphism, and a CT60A/G, both of which are within the 3 0 -untranslated region.…”
Section: Introductionmentioning
confidence: 99%
“…16 In contrast, association studies using a C/T SNP in the promotor of CTLA-4 at position -318 (C/T À318 ) were less consistent with some showing association 25 and others not. 24 CTLA-4 was also reported to be associated with HT in various populations including Caucasians 10,20 and Japanese, 13 although some studies did not find this. 19,23,24 Vaidya et al 26 reported linkage to the CTLA-4 gene region on chromosome 2q33 in families with GD using nonparametric linkage analysis.…”
Section: Introductionmentioning
confidence: 99%